2015
DOI: 10.1121/1.4920642
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluations of a noise control for roof bolting machines

Abstract: Roof bolting machine (RBM) noise is a significant health hazard in underground coal mining because the sound levels at the operator’s station often exceed 100 dB(A). Drilling the hole prior to installing a roof bolt is the most significant source of RBM operator noise exposure. The dominant source of drilling noise is the drill steel. NIOSH has developed an enclosure to surround the drill steel as it is drills the hole to reduce the noise reaching the machine operator. The collapsible drill steel enclosure, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additionally, 12 case studies were collected reporting on 107 uncontrolled studies of engineering control interventions (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) . In most cases (41) , authors evaluated design changes, followed by installing damping material and silencers (21) , purchasing new equipment (17) , using enclosures (15) , installing acoustic panels and curtains (13) , and maintenance only (7) .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 12 case studies were collected reporting on 107 uncontrolled studies of engineering control interventions (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) . In most cases (41) , authors evaluated design changes, followed by installing damping material and silencers (21) , purchasing new equipment (17) , using enclosures (15) , installing acoustic panels and curtains (13) , and maintenance only (7) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to regulatory measures, successful noise‐reducing equipment and methods have been developed/identified within Mining. Engineering controls, such as modified tail sections of continuous mining machines, noise control packages for vibrating screens, applying noise barriers and absorptive treatments within talc processing plants, drill bit isolators for roof bolting machines, structural modifications to cutting drums of longwall shearers, and noise control packages for vibrating screens, have shown to decrease noise emitted by equipment, while also maintaining durability. A 2009 study found that new‐style haul truck cabs used in limestone mines were significantly quieter (65.1 dBA) than old‐style (84.8 dBA) and retro‐fitted cabs (84.9 dBA) with the windows closed .…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed engineering controls have shown great promise in reducing equipment noise within mining . Incorporation and continued development of these technologies, both in Mining and OGE, is critical for reducing worker exposures, in addition to employing effective administrative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Underground testing of the drill bit isolator showed noise levels at the operator's location were reduced by 3 dB when compared to baseline drilling. 12 Additional engineering noise controls that NIOSH has developed include the following: Partial cabs for surface water well drills. Collapsible drill steel enclosure for roof bolting machines.…”
Section: Engineering Noise Controlsmentioning
confidence: 99%
“…Underground testing of the drill bit isolator showed noise levels at the operator's location were reduced by 3 dB when compared to baseline drilling. 12 Additional engineering noise controls that NIOSH has developed include…”
Section: Engineering Noise Controlsmentioning
confidence: 99%